Metabolic engineering of thermophilic Bacillus methanolicus for riboflavin overproduction from methanol. Issue 5 (25th March 2023) - Klein, Vivien Jessica; Brito, Luciana Fernandes; Perez‐Garcia, Fernando; Brautaset, Trygve; Irla, Marta
Abstract: The growing need of next generation feedstocks for biotechnology spurs an intensification of research on the utilization of methanol as carbon and energy source for biotechnological processes. In this paper, we introduced the methanol‐based overproduction of riboflavin into metabolically engineered Bacillus methanolicus MGA3. First, we showed that B. methanolicus naturally produces small amounts of riboflavin. Then, we created B. methanolicus strains overexpressing either homologous or heterologous gene clusters encoding the riboflavin biosynthesis pathway, resulting in riboflavin overproduction. Our results revealed that the supplementation of growth media with sublethal levels of chloramphenicol contributes to a higher plasmid‐based riboflavin production titre, presumably due to an increase in plasmid copy number and thus biosynthetic gene dosage. Based on this, we proved that riboflavin production can be increased by exchanging a low copy number plasmid with a high copy number plasmid leading to a final riboflavin titre of about 523 mg L −1 in methanol fed‐batch fermentation. The findings of this study showcase the potential of B. methanolicus as a promising host for methanol‐based overproduction of extracellular riboflavin and serve as basis for metabolic engineering of next generations of riboflavin overproducing strains. Abstract : In this work we present engineering of thermophilic Bacillus methanolicus for methanol‐based riboflavin overproduction. Using high copy number plasmid we created a strain producing 523 mg L‐1 riboflavin in methanol fed‐batch fermentation.